Pembinaan Remaja Putus Sekolah di Panti Sosial Bina Remaja Harapan Padang Panjang - Arnada, Septia Stri; Afrinaldi, Afrinaldi; Charles, Charles; Rahmi, Alfi (TSAQOFAH, 2023)
Guidance for dropout youth is an effort, action and activity to direct personality, abilities and skills through non-formal education. Teenagers dropping out of school is a severe problem that needs attention by the government so that the unemployment rate caused by dropping out of school does not increase and minimizes social problems caused by teenagers who fall out of school due to a lack of direction and do not get a good education. The purpose of this study was to see how the guidance provided by social institutions for youth development to adolescents dropping out of school. This research is field research (field research) with a qualitative descriptive approach. The key informants were 1 supervisor of the social institution for fostering hopeful youth in Padang Panjang and a support informant for the child of the social institution for promoting hope for young people in Padang Panjang. Data were collected through interview guides, observation and documentation. After the data was collected, the authors carried out the process of analyzing the data using a qualitative descriptive analysis. Based on the research that has been done, it is known that a lot of coaching is given to out-of-school youth in the form of social, mental, physical, and skilled guidance. Skills guidance is provided in the form of sewing skills and embroidery. The supporting factors of the coaching program are a budget, a strong will from youth, and the availability of adequate facilities and infrastructure.